Le défi de l’appropriation de la responsabilité sociale des entreprises (RSE) par des syndicats nationaux : les leçons de la Coalition québécoise contre les ateliers de misère (CQCAM) - Emmanuelle Champion (Revue de la Régulation)
Can a multi-stakeholder coalition promote ownership by national unions of Corporate Social Responsibility (CSR) and its practices? In 2003, a major Canadian private sector union created, with several other civil society actors, the Coalition Québécoise contre les Ateliers de Misère (CQCAM), with the mandate to raise public awareness of their existence and develop alternatives to counter their proliferation. Very quickly, this Coalition participated in the development and dissemination in Québec of responsible procurement practices. By mobilizing the Perspective of institutional logics (Thornton, Ocasio and Lounsbury, 2012) and various works situating social movements within institutional processes, this article highlights the tensions, contradictions and obstacles with which the union actor must cope when it participates in the implementation of CSR. To do this, we define a multi-stakeholder coalition as an institutional bricoleur who can bridge the union logic with the logic of CSR at different levels. If the participation of social movements is seen as a necessary condition for the emergence of a regulatory system capable of controlling the global supply chains, our results account for the moderating action of the institutional embeddedness of the union actor (« The Embedded Agency ») on its ability to appropriate CSR, despite its voluntarism.